2019
DOI: 10.25035/jade.01.01.03
|View full text |Cite
|
Sign up to set email alerts
|

“Support is What Really Helped Me Get Through”: Understanding Athletes’ Online Disclosures about Pursuit and Receipt of Social Support During Concussion Recovery

Abstract: This research examines the role of social support in athletes' lived experiences with concussion injuries. Fifty-eight blog posts authored by athletes documenting their concussion injuries were analyzed to determine the types of support athletes sought and received while rehabilitating from a concussion. A deductive approach guided by Xu and Burleson's (2001) social support typology guided analysis of the blog posts. Results indicated that to varying degrees, athletes sought and received emotional, information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Mclaren and Spink suggested that there may be a link between the degree to which athletes exchange information (at the individual and team levels) and team performance outcomes (i.e., wins or losses) [5]. Sanderson and Cassilo explored the role of social support in the life experience of athletes with concussion injuries [6]. ese methods provide some references for our research, but due to the short time and small sample size of the relevant research, they have not been recognized by the public.…”
Section: Related Workmentioning
confidence: 99%
“…Mclaren and Spink suggested that there may be a link between the degree to which athletes exchange information (at the individual and team levels) and team performance outcomes (i.e., wins or losses) [5]. Sanderson and Cassilo explored the role of social support in the life experience of athletes with concussion injuries [6]. ese methods provide some references for our research, but due to the short time and small sample size of the relevant research, they have not been recognized by the public.…”
Section: Related Workmentioning
confidence: 99%
“…Participants described the significance of social factors for both the “symptom persistence loop” and the “recovery pathway,” which is consistent with evidence of both social support and social pressure impacting outcomes (i.e., return to play; van Ierssel et al, 2022). Additionally, young adults with concussion often emphasize the benefit of, and sometimes unmet need for, social support in their recovery experiences (Bannon et al, 2020; Sanderson & Cassilo, 2019; Seguin & Culver, 2022). This finding places the fear–avoidance model in a broader social-ecological context and suggests the potential benefit of including social factors in treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…1,9 These barriers are evident in the physical domain such as joint and muscle pain, stiffness, or lack of flexibility 10,13,46 but also extend into the psychological and social domains such as fear of reinjury, kinesiophobia, and low quality of social support. 1,38,50,53,55 Prospective and longitudinal designs would aid in extending our understanding of potential between-group differences based on injury type as high school athletes navigate the challenges and barriers of their long-term participation in sport and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that multiple stakeholders are typically leaned on by athletes for social support, and this need is compounded after an athlete sustains an SRI. 50,61 Facilitating communication between supporting individuals—including athletic trainers, coaches, parents, and school nurses—that emphasizes a sensitivity to domain-specific areas of potential deficits can aid in treatment while strengthening the effectiveness and efficiency of the athlete’s support systems. 7,26 Additionally, these increasing trajectories of health following the recovery timeline in our study may differ from injuries with more prolonged, fluctuating recoveries or season-ending injuries, such as patients recovering from anterior cruciate ligament reconstruction.…”
Section: Discussionmentioning
confidence: 99%